Предмет: Алгебра, автор: yamsik

помогите пожалуйста ​

Приложения:

Ответы

Автор ответа: bokachi38
0

(m + 2)(m + 2) =  m \times m  + m \times 2+ 2 \times m + 2 \times 2 =  {m}^{2}  + 4m + 4 \\ (3 + p)(3 + p) = 3 \times 3 + 3 \times p + p \times 3 + p \times p = 9 + 6p +  {p}^{2}  \\ (2a + b)(2a + b) = 2a \times 2a + 2a \times b + b \times 2a + b  \times b =  {4a}^{2} + 4ab +  {b}^{2}   \\ (5 + c)(5 + c) = 5 \times 5 + 5 \times c + c \times 5 + c \times c = 25 + 10c +  {c}^{2}

Похожие вопросы
Предмет: Английский язык, автор: 123456w
Предмет: Английский язык, автор: 123456w
Предмет: Алгебра, автор: Аноним